1987
DOI: 10.1007/bf00270417
|View full text |Cite
|
Sign up to set email alerts
|

Residual insulin production, glycaemic control and prevalence of microvascular lesions and polyneuropathy in long-term Type 1 (insulin-dependent) diabetes mellitus

Abstract: The aim of the present study was to evaluate the role of residual insulin production in long-term Type 1 (insulin-dependent) diabetes mellitus. Ninety-seven patients with a disease duration of 9-16 years and onset before the age of 30 years were studied. C-peptide excretion in 24-h urine samples was measured as an indicator of residual insulin production. Thirty-five patients (36%) excreted C-peptide (greater than or equal to 0.2 nmol); as many as possible of them were carefully matched with a non-excretor pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 28 publications
2
66
1
Order By: Relevance
“…The C-peptide level differed significantly from that of the placebo-treated control group at 12 and 18 months. This finding is of interest since it has been previously shown that the presence of minute residual (3-cell function in patients with longterm IDDM confers better glycemic control (11)(12)(13), which in itself according to the evidence presented from the Diabetes Control and Complications Trial is associated with a remarkable reduction in the risk of long-term complications (14). In the present study of 20 patients, no difference in metabolic control between the two treatment groups was observed.…”
Section: Discussionmentioning
confidence: 80%
“…The C-peptide level differed significantly from that of the placebo-treated control group at 12 and 18 months. This finding is of interest since it has been previously shown that the presence of minute residual (3-cell function in patients with longterm IDDM confers better glycemic control (11)(12)(13), which in itself according to the evidence presented from the Diabetes Control and Complications Trial is associated with a remarkable reduction in the risk of long-term complications (14). In the present study of 20 patients, no difference in metabolic control between the two treatment groups was observed.…”
Section: Discussionmentioning
confidence: 80%
“…As a consequence, individuals with type 1 diabetes have severely reduced levels or absence of C-peptide; this is considered an important factor in the pathophysiology of diabetic complications. In fact, people with type 1 diabetes who retain a low but detectable level of C-peptide are less prone to develop microvascular complications of the eyes, kidneys and peripheral nerves [24][25][26]. Moreover, pancreas or islet transplantation, with restoration of endogenous insulin and C-peptide secretion, is known to be accompanied by improvement of diabetes-induced abnormalities of nerve function, endothelial function and both structural and functional changes of the kidneys [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…C-peptide, the cleavage product of the proinsulin molecule in the pancreatic beta cells, has been shown to exert insulin-independent biological effects on a number of cells, proving itself as a bioactive peptide with antiinflammatory properties [23]. As type 1 diabetes patients typically lack physiological levels of insulin and C-peptide, this is considered an important factor in the pathophysiology of diabetic complications [24][25][26]. C-peptide has been shown to improve endothelial dysfunction and systemic inflammation in several in vivo and in vitro models of inflammation-mediated vascular injury by reducing expression of genes encoding endothelial cell adhesion molecules, inflammatory cytokine production and adherence and transmigration of leucocytes [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Residual insulin secretory activity in these patients has been suggested to be associated with improved blood glucose control in cornparison with patients without such activity [15,16]. Likewise, early signs of microvascular lesions are observed more frequently in patients without signs of residual beta-cell activity [14]. In addition, a negative relationship has been demonstrated between endogenous beta-cell activity and early signs of diabetic retinopathy, as evaluated by vitreous fluorophotometry; this correlation was more marked than that between glycaemic control and early retinopathy [17].…”
Section: Introductionmentioning
confidence: 98%
“…Some patients with IDDM maintain a level of pancreatic beta-cell activity for many years after onset of the disease [13,14]. Residual insulin secretory activity in these patients has been suggested to be associated with improved blood glucose control in cornparison with patients without such activity [15,16].…”
Section: Introductionmentioning
confidence: 99%